Artificial intelligence : a modern approach - Russell, Stuart J. (Upper Saddle River, New Jersey : Prentice-Hall, 2010)
The long-anticipated revision of this best-selling text offers the most comprehensive, up-to-date introduction to the theory and practice of artificial intelligence.
Previous edition: Upper Saddle River, N.J.: Prentice Hall, 2003.